Gully intrusion into reclaimed slopes: a long-term averaged calculation procedure - Thornton, Christopher I., author; Abt, Steven R., advisor; Watson, Chester C., committee member; Smith, Freeman M., committee member; Arneson, Larry A., committee member (Colorado State University. Libraries, 1999)
Increased environmental concern throughout the United States has renewed the importance of mined land reclamation and disposal of wastes associated with the excavation and processing of natural resources such as coal, uranium and other minerals. The Surface Mining Control and Reclamation Act of 1977, Public Law 95-87, requires mining companies to restore the approximate original contour of the land in a manner that prevents slides, erosion, and water pollution. The Uranium Mill Tailings Radiation Control Act of 1978, Public Law 95-604, outlines measures to stabilize radioactive byproducts and restoration of mine sites from which these materials were removed. The restoration of mined land and long-term stabilization of waste disposal areas is of priority to protect public health, safety and conserve other natural resources, such as soil and water. Current regulations (40 CFR 192) require the waste to remain undisturbed, usually for periods of 200 to 1,000 years. The impoundments constructed to encapsulate the waste materials must resist the natural erosive processes to prevent exposure and release of the waste. One erosive process that has been difficult to predict is gully intrusion. This study was conducted to analyze the gully erosion processes and determine its effect on long-term embankment stability and estimate the potential impacts on waste stabilization. The investigation was conducted in four distinct phases: (1) literature search and background information collection; (2) performance of a laboratory simulation study; (3) field data collection; and (4) data compilation, analysis, and synthesis. A comprehensive procedure has been presented for estimating the magnitude and location of a potential gully intrusion into a soil covered, waste impoundment. The estimation procedure requires that the user obtain information pertaining to the regional hydrology, soil characteristics, proposed impoundment geometry, and design life. It is noted that while a limited set of field data was available for synthesis into the prediction equations, the procedure presented is a first step into the determination of the magnitude and location of gullying into sloped surfaces.
Keywords: civil engineering; environmental science